Hiding violence to deal with the state: Criminal pacts in El Salvador and Medellin. (March 2016) - Cruz, José Miguel; Durán-Martínez, Angélica
In 2012, the two major street gangs in El Salvador, Mara Salvatrucha 13 and Barrio 18, struck a truce credited with reducing homicide rates by more than 50% in one year. Although the gang truce held for only 18 months, the significant reduction in homicides puzzled observers that believed youth gangs were unable to coordinate violence, especially considering that previous and similar efforts aimed at striking agreements did not achieve similar results. This article addresses a question posed by the puzzle of the Salvadoran truce's success: under what conditions do negotiations between or with criminal organizations effectively reduce criminal violence? By comparing truces and criminal pacts in El Salvador and in Medellin, Colombia, we argue that criminal pacts can reduce homicides when (a) they directly involve the state as an administrator of incentives to reduce violence and (b) criminal organizations have achieved organizational cohesion and leadership that facilitate territorial control and strategic dependability. These conditions allow organizations to regulate violence. Our argument highlights the importance of how violence is performed and, more importantly, its visibility, to fully understand criminal behavior within pacts. It also points to potential lessons for countries seeking alternatives to reduce criminal and political violence in Latin America and elsewhere.